Emotion recognition dysfunction after anesthesia and cardiac surgery - Zhang, Delin; Shen, Yi; Chen, Zhiyun; Guo, Yang; Gao, Zaifeng; Huang, Jian; Lu, Xiqian (Frontiers in Psychology, 2022)
Cognitive dysfunction after anesthesia and surgery has long been recognized. Recently, researchers provided empirical evidence for social cognition dysfunction (SCD) after anesthesia and surgery. In the present study, we concentrated on the deficits in emotion recognition, one of the most important clinical perspectives in SCD, in patients who underwent cardiac surgery. Biological motion (BM) was considered as the stimulus of interest, and patients’ abilities of BM emotion perception and action perception before and after anesthesia and surgery were examined. In total, 60 adult patients (40-72 years old) completed the BM recognition task, which required them to label the types of actions and emotions of perceived BM. The results showed that while action perception remained intact after cardiac surgery, 18.3% of patients exhibited deficits in emotion perception, further confirming the existence of SCD after anesthesia and surgery.